Pengaruh Harga, Kualitas Produk, dan Promosi terhadap Keputusan Pembelian Melalui Shopee pada Mahasiswa di Pekalongan - Firdan, Mohammad; Artanto, Fenilinas Adi (CV. Kalimasada Group, 2024)
Technological developments have reached into economic activities. Currently, people are starting to switch to using technology in carrying out buying and selling activities. Buying and selling activities are now facilitated by e-commerce. Currently, there are many e-commerce service providers, one of which is Shopee. Research using quantitative descriptive methods was used on Shopee marketplace users with the aim of finding out how price, product quality, promotions influence purchasing decisions through the Shopee marketplace. The population of this research consists of students who have made purchases through Shopee, who were selected using the Purposive Sampling method and a questionnaire distributed via Google Form. Data analysis was carried out through descriptive analysis techniques and inferential analysis using Partial Least Square (PLS) as an analysis tool. The research results show that price and product quality do not have a significant influence on purchasing decisions, while promotions have a significant and positive influence on purchasing decisions. It was also found that price, product quality and promotion only had a 52.3% influence on purchasing decisions via Shopee among students in Pekalongan.